Prinsip-Prinsip Manajemen Keuangan Sekolah Di SDN Inpres Silae - Yuli Larasati; Juliana Kadang; Muslimin Muslimin; Muh.Riswandi Palawa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study was conducted with the aim of knowing how the implementation of the principles of financial management listed in Law No. 20 of 2003 article 48. Transparency can mean openness, with transparency it can increase the support of parents, the community and the government. Accountability means that the use of financial resources can be accounted for in accordance with the plan that has been set at the SDN inpres Silae school.